2022
DOI: 10.48550/arxiv.2208.02477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread Detection of Two Components in the Hot Circumgalactic Medium of the Milky Way

Abstract: Surrounding the Milky Way (MW) is the circumgalactic medium (CGM), an extended reservoir of hot gas that has significant implications for the evolution of the MW. We used the HaloSat all-sky survey to study the CGM's soft X-ray emission in order to better define its distribution and structure. We extend a previous HaloSat study of the southern CGM (Galactic latitude b < −30 • ) to include the northern CGM (b > 30 • ) and find evidence that at least two hot gas model components at different temperatures are req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(95 reference statements)
2
1
0
Order By: Relevance
“…Observations of the Milky Way halo report a temperature component around ∼ 10 6.3 K (Bluem et al 2022), which is roughly consistent with the second peak observed in the TNG50 temperature distributions. In addition, observational studies infer gas phases as hot as ∼ 10 6.5 K (southern galactic sky Kaaret et al 2020) and ∼ 10 6.9 K (northern galactic sky Bluem et al 2022) in the Milky Way halo, albeit the abundance of these phases is uncertain.…”
Section: Ranges Of Variation Of Tng50 Cgm Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…Observations of the Milky Way halo report a temperature component around ∼ 10 6.3 K (Bluem et al 2022), which is roughly consistent with the second peak observed in the TNG50 temperature distributions. In addition, observational studies infer gas phases as hot as ∼ 10 6.5 K (southern galactic sky Kaaret et al 2020) and ∼ 10 6.9 K (northern galactic sky Bluem et al 2022) in the Milky Way halo, albeit the abundance of these phases is uncertain.…”
Section: Ranges Of Variation Of Tng50 Cgm Propertiessupporting
confidence: 83%
“…Observations of the Milky Way halo report a temperature component around ∼ 10 6.3 K (Bluem et al 2022), which is roughly consistent with the second peak observed in the TNG50 temperature distributions. In addition, observational studies infer gas phases as hot as ∼ 10 6.5 K (southern galactic sky Kaaret et al 2020) and ∼ 10 6.9 K (northern galactic sky Bluem et al 2022) in the Milky Way halo, albeit the abundance of these phases is uncertain. The temperature of gas within the eROSITA bubble(s) (see Introduction) has been inferred to be about 10 6.5 K with Suzaku (Kataoka et al 2013) and 10 6.6−6.7 K from the modelling of OVII and OVIII emission lines (Miller et al 2016).…”
Section: Ranges Of Variation Of Tng50 Cgm Propertiessupporting
confidence: 83%
“…The abundance Z and the galactic absorption 𝑁 𝐻 were fixed, following Mantz et al (2022). A fit with a third thermal component of ∼ 0.6𝑘𝑒𝑉 was also attempted (Urban et al 2014;Bluem et al 2022, see e.g. ), but this did not result in an improved fit.…”
Section: Markevitch 2006mentioning
confidence: 99%